Cobalt(II), Nickel(II) and Copper(II) Complexes of 1-Hydroxy-2-Naphthyl(4-X-Styryl) Ketoneoximes - Tharmaraj, P.; Sheela, C.D.; Natarajan, C. (Asian Journal of Chemistry, 2010)
Metal complexes of the type ML2 [M = Co(II), Ni(II), Cu(II); L = 1-hydroxy-2-naphthyl( 4-X -styryl)ketoneoximes (HNXSKOx), (X = H, Me, MeO)] have been synthesized. All the chelates are anhydrous. The copper complexes possess trans-square-planar geometry and the nickel and cobalt complexes have low-spin transsquare- planar configuration. As the conjugation of C=N with Ph—C=C is inhibited, the basic nature of oximino nitrogen is not affected. The strong M—N σ-bond leads to enhanced ligand field strength and spin-pairing.